Advances in Human Factors in Cybersecurity Proceedings of the AHFE 2017 International Conference on Human Factors in Cybersecurity, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Nicholson, Denise (Advances in Intelligent Systems and Computing, 2018)
This book reports on the latest research and developments in the field of cybersecurity, placing special emphasis on personal security and new methods for reducing human error and increasing cyber awareness, as well as innovative solutions for increasing the security of advanced Information Technology (IT) infrastructures. It covers a broad range of topics, including methods for human training; novel Cyber-Physical and Process-Control Systems; social, economic, and behavioral aspects of cyberspace; issues concerning the cybersecurity index; security metrics for enterprises; risk evaluation, and many others. Based on the AHFE 2017 International Conference on Human Factors in Cybersecurity, held on July 17-21, 2017, in Los Angeles, California, USA, the book not only presents innovative cybersecurity technologies, but also discusses emerging threats, current gaps in the available systems, and future challenges that may be successfully overcome with the help of human factors research. .